Health Literacy and Infectious Disease Control: Community, Policy, and Digital Strategies for Prevention and Management - Febriani, Isyfi Salwa; Nugrahani, Marshanda Rimadita (Journal of Health Literacy and Qualitative Research, 2022)
Health literacy is a fundamental determinant of infectious disease prevention and management, influencing individuals' ability to access, understand, and utilize health information effectively. This study systematically reviews the impact of health literacy on disease prevention behaviors, treatment adherence, and healthcare accessibility. A comprehensive literature search was conducted across major academic databases, including PubMed, Scopus, and Google Scholar, focusing on peer-reviewed studies published in the past decade. Findings indicate that higher health literacy levels are associated with improved compliance with preventive measures, such as vaccination and hygiene practices, while lower literacy levels contribute to misinformation susceptibility and inadequate healthcare utilization. Community-based interventions, educational policies, and digital health strategies have demonstrated significant effectiveness in enhancing health literacy, particularly in vulnerable populations. However, disparities persist due to socioeconomic barriers, limited access to digital resources, and inconsistent policy implementation across different healthcare systems. Addressing these challenges requires multi-sectoral collaboration, increased investment in public health education, and the integration of digital literacy initiatives. Future research should explore innovative approaches, such as artificial intelligence-driven health education tools, to further improve accessibility and engagement. Strengthening health literacy remains a vital strategy in enhancing global health resilience and reducing the burden of infectious diseases.